Produk Kemasan Tanpa Label Halal di Surabaya perspektif Undang-Undang Nomor 8 Tahun 1999, Undang-Undang Nomor 33 Tahun 2014, dan Maqāṣid al-Sharī‘ah - Sanuri, Sanuri; Ayu Ningtiyas, Mega (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2024)
Abstract: This is a field research that discusses packaging products without the halal label in Surabaya under the perspective Law Number 8 of 1999, Law Number 33 of 2014 and Maqāṣid al-Sharī‘ah. Data collection techniques in this study were carried out using three ways, namely: (1) interviews; (2) observation and; (3) documentation. From all the descriptions presented, the results of this study are as follows: Based on the analysis of the Law No. 8 of 1999 and Law. No. 33 of 2014, the practice carried out by business actors in the modern market of Surabaya has not followed the provisions for halal production in the form of including halal writing on food labels. Whereas, in the perspective of Maqāṣid al-Sharī‘ah, what business actors do is contrary to the principles of monotheism and ta'abbudi (servitude to Allah SWT), because consuming halal and tayyib products is an order for Muslim consumers. In addition, the circulation of products without halal label in Surabaya has the potential to damage some of the joints in Maqāṣid al-Sharī‘ah features such as religion, soul and reason. Keywords: Business actors; halal products; halal label; Maqāṣid al-Sharī‘ah. Abstrak: Penelitian lapangan (field research) yang membahas tentang produk kemasan tanpa lebel halal di Surabaya perpektif Maqāṣid al-Sharī‘ah dan Undang-Undang Nomor 8 tahun 1999 dan Undang-Undang Nomor 33 tahun 2014. Adapun tehnik pengumpulan data dalam penelitian ini dilakukan dengan menggunakan tiga cara, yaitu: (1) wawancara; (2) observasi dan; (3) dokumentasi. Dari seluruh uraian yang disajikan, maka hasil dari penelitian ini adalah sebagai berikut: Berdasarkan analisis UU. No. 8 tahun 1999 dan UU. No. 33 tahun 2014, praktik yang dilakukan oleh para pelaku usaha di pasar modern Surabaya belum mengikuti ketentuan berproduksi secara halal dalam bentuk pencantuman tulisan halal pada label makanan. Sedangkan dalam perspektif Maqāṣid al-Sharī‘ah, apa yang dilakukan oleh para pelaku usaha bertentangan dengan prinsip tauhid dan ta‘abbudī (penghambaan kepada Allah SWT), karena mengkonsumsi produk halal dan tayyib adalah perintah bagi konsumen Muslim. Selain itu, peredaran produk tanpa label halal di Surabaya sangat berpotensi merusak beberapa sendi yang ada dalam fitur-fitur Maqāṣid al-Sharī‘ah seperti agama, jiwa dan akal. Kata Kunci: Pelaku Usha; Produk Halal; Label Halal; Maqāṣid al-Sharī‘ah.